Postnatal Protein Malnutrition Induces Neurochemical Alterations Leading to Behavioral Deficits in Rats: Prevention by Selenium or Zinc Supplementation. - Adebayo, Olusegun (Taylor and Francis, 2014)
Background/objectives: Protein malnutrition (PM) is a worldwide problem affecting brain development in a large number of children. The present study was aimed at studying the perturbations in antioxidant defense system resulting from protein deficiency and to evaluate the preventive effect of Se and Zn on cortex and cerebellum. Methods: Well-fed (WF) and PM rats were fed on 16 and 5% protein diet, respectively. After 10 weeks, animals were supplemented with Se and Zn at a concentration of 0.15 and 227 mg/l in drinking water for 3 weeks. Results: PM rats showed significant increase in lipid peroxidation, nitrite, and protein carbonyl levels. Reduction in the activity of antioxidant enzymes, thiol levels, GSH/GSSG ratio, and neurobehavioral deficits were observed in PM groups. Se and Zn supplementation reduced the levels of lipid peroxidation, nitrite, and protein carbonyl and restored the activity of antioxidant enzymes and thiol levels in the cortex and cerebellum of PM rats along with neurobehavioral deficits. Discussion: The study showed that Se and Zn supplementation might be beneficial in preventing biochemical alterations and neurobehavioral deficits in PM children.
Keywords: Behavior, Brain; Oxidative stress; Protein malnutrition; Selenium; Zinc